Human capital management in a pandemic and crisis - S. K. Baуdybekova (Управление)
The article reflects the main problems of the development and formation of human capital and its reassessment in the context of a pandemic COVID-2019. In the context of economic management during the pandemic, the demand for human capital has increased. The most demanded personnel, as time has shown, are the medical workers, as well as the workers who ensure biological safety.The aim of the research is studying the issues of management and development of human capital, both in theoretical and practical aspects. The following tasks were completed: an analysis of the development and formation of human capital was carried out, the relationship between the intellectual capital, the level of education, personal incomes of subjects in a pandemic was analysed. The topic of the article is relevant and new due to the fact that in connection with the ongoing crisis phenomena in the form of a pandemic, an overestimation of human capital took place. The labor market is undergoing global and significant changes due to the emerging force majeure conditions.The study used methods of comparison, logical reasoning, and expert assessments. The article may be of interest to researchers in the field of economics and labor organization, as well as specialists in the field of studying labor markets and economic policy.